Antimicrobial Activity of The Ethanol Extract of Coffea canephora L. Seeds Against Staphylococcus aureus and Propionibacterium acnes - Siska Elisahbet Sinaga; Matius Paundanan; Maharani Farah Dhifa Dg Masikki; Diana Widiastuti (Helium: Journal of Science and Applied Chemistry, 2023)
Acne is a skin disease that causes humans to lack confidence in carrying out activities. Besides being sick, acne worsens the beauty of human skin. The cause of acne is gram-positive bacteria, namely Staphylococcus aureus and Propionibacterium acnes. Many studies reported that Coffea canephora L can inhibit the growth of bacteria. The objective of this study is to establish the minimum inhibitory concentration (MIC) of the ethanol extract of robusta coffee seeds in inhibiting the growth of Staphylococcus aureus and Escherichia coli. The ethanol extract of C. canephora L seed was obtained by maceration method using 96% ethanol. The extract obtained was evaluated for its antibacterial activity using the agar diffusion method with perforation techniques. The extract was divided into five various concentrations (50%, 25%, 12.5%, 6.25%, and 3.125%). The results of this study indicated that the ethanol extract of coffee seeds with a concentration of 50% resulted in a wider diameter of the zone of inhibition of bacterial growth in S. aureus, 30.00 mm compared to P. acnes, 26.22 mm. The MIC of ethanol extract for S. aureus at 3.00%Â  while P. acnes was 6.00%.Â  In conclusion, the antibacterial effect of the ethanol extract of coffee seeds at 50% concentration was stronger against S. aureus bacteria than P. acnes. The greater the concentration of the extract, the wider the resulting inhibition zone.